Economic Law and Standardization: A Basis for Avoiding Risks in Business - Трофанчук, Григорій Іванович; Трофанчук, Г. І.; Трофанчук, Григорий Иванович; Trofanchuk, Hryhorii I.; Trofanchuk, Hryhoriy I.; Попович, Тетяна Григорівна; Попович, Т. Г.; Попович, Татьяна Григорьевна; Popovych, Tetiana H.; Popovych, Tetiana G.; Безух, Олександр Васильович; Безух, О. В.; et al. (Lifescience Global, 2021)
Currently, in Ukraine, there is a system of technical regulation as part of the general system of standardization. Technical regulation is defined as a means of state regulation, which, like any legal regulation, is implemented by appropriate legal means. This explains the relevance of this study. This paper investigates the Economic Code of Ukraine, several Ukrainian laws (the Law of Ukraine "On Environmental Audit", the Law of Ukraine "On Standardization", the Law of Ukraine "On Technical Regulations and Conformity Assessment", etc.), and State standards. Technical regulation was also considered as a general category and a legal phenomenon, as a result of which it was noted that the technical regulation adopted in Ukraine for dividing products into food and non-food products is only a matter of supervision over the conformity of goods and the use of conditions for a specific legal act and type of product. It was concluded that standardization proceeds from social regulation and generates norms of a technical, organizational, or other orderly nature, transforming into legal provisions. Therewith, technical regulation also derives from legal regulation and gives rise to technical guidelines, which constitute statutory regulations that form part of the national legislation of Ukraine, including economic legislation. As a result, it is proposed to improve and supplement the wording of Part 2 Article 16 of the Law of Ukraine "On Standardization", and it is also proposed to reword Article 24 of the Law of Ukraine "On Technical Regulations and Conformity Assessment".

Нині в Україні діє система технічного регулювання як частина загальної системи стандартизації. Технічне регулювання визначається як засіб державного регулювання, який, як і будь-яке правове регулювання, реалізується відповідними правовими засобами. Це пояснює актуальність цього дослідження. У цій роботі досліджуються Господарський кодекс України, декілька законів України (Закон України «Про екологічний аудит», Закон України «Про стандартизацію», Закон України «Про технічні регламенти та оцінку відповідності» тощо), а також Державні стандарти. Технічний регламент також розглядався як загальна категорія та правове явище, внаслідок чого було зазначено, що прийнятий в Україні технічний регламент поділу продукції на продовольчі та непродовольчі товари є лише питанням нагляду за відповідністю товарів і використання умов для конкретного правового акту та виду продукції. Зроблено висновок, що стандартизація виходить із соціального регулювання і породжує норми технічного, організаційного чи іншого впорядкованого характеру, трансформуючись у правові положення. При цьому технічне регулювання також випливає з правового регулювання та породжує технічні вказівки, які є нормативними актами, що є частиною національного законодавства України, у тому числі господарського законодавства. У зв’язку з цим пропонується удосконалити та доповнити редакцію частини 2 статті 16 Закону України «Про стандартизацію», а також статтю 24 Закону України «Про технічні регламенти та оцінку відповідності».
Popovych T. G. Economic Law and Standardization: A Basis for Avoiding Risks in Business / T. G. Popovych, O. V. Bezukh, H. I. Trofanchuk, T. B. Pozhodzhuk // International Journal of Criminology and Sociology. - № 10. - Lifescience Global, 2021. - Р. 440-449.
Keywords: technical regulation; laws of Ukraine; state standards; ISO; regulations; технічний регламент; закони України; державні стандарти; Міжнародна організація зі стандартизації; регламенти; Research Subject Categories::LAW/JURISPRUDENCE